2023
DOI: 10.1002/advs.202304084
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Immune Landscape Remodeling Unravels the Underlying Mechanism for Synchronized Muscle and Bone Aging

Pengbin Yin,
Ming Chen,
Man Rao
et al.

Abstract: Evidence from numerous studies has revealed the synchronous progression of aging in bone and muscle; however, little is known about the underlying mechanisms. To this end, human muscles and bones are harvested and the aging‐associated transcriptional dynamics of two tissues in parallel using single‐cell RNA sequencing are surveyed. A subset of lipid‐associated macrophages (triggering receptor expressed on myeloid cells 2, TREM2+ Macs) is identified in both aged muscle and bone. Genes responsible for muscle dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Nevertheless, previous studies have demonstrated that the absence or pharmacological inhibition of OPN, as well as bone marrow transplantation in OPN -/mice, can mitigate the ATM senescence-like phenotype, ultimately restoring healthy adipose tissue homeostasis in the context of aging [20]. The SPP1 gene, implicated in muscular dystrophy and bone loss, exhibits high expression in TREM2+ lipid-associated macrophages, suggesting its conserved role in age-related characteristics [21]. Similar findings in macrophages were observed in the analysis of intercellular communication data from single-cell RNA-sequencing data of skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, previous studies have demonstrated that the absence or pharmacological inhibition of OPN, as well as bone marrow transplantation in OPN -/mice, can mitigate the ATM senescence-like phenotype, ultimately restoring healthy adipose tissue homeostasis in the context of aging [20]. The SPP1 gene, implicated in muscular dystrophy and bone loss, exhibits high expression in TREM2+ lipid-associated macrophages, suggesting its conserved role in age-related characteristics [21]. Similar findings in macrophages were observed in the analysis of intercellular communication data from single-cell RNA-sequencing data of skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%